Association Between Ambulatory Care Utilization and Coronary Artery Disease Outcomes by Race/Ethnicity - Kim, Eun Ji (J Am Heart Assoc, 2019)
BACKGROUND: Coronary artery disease is common, and there exist disparities in management and outcomes. The purpose of this study is to examine the association between ambulatory care utilizations and inpatient acute myocardial infarction (AMI) mortality. METHODS AND RESULTS: This is a retrospective analysis of a stratified national sample of Medicare fee‐for‐service enrollees aged 66 years and older from January 1, 2010 to December 31, 2011. We measured both number of ambulatory visits and presence of ambulatory cardiac tests. The primary outcome was inpatient AMI mortality. Using multivariate logistic regression models, we estimated the association between ambulatory care utilization and the main patient outcomes, adjusting for patient‐ and area‐level demographic, geographical, and clinical characteristics. We found that a significantly lower percentage of Hispanics and Asians, relative to whites, had frequent ambulatory care visits. Among the largest 4 race/ethnic groups, Asians had the highest observed inpatient mortality rate (15.9%). Overall, low ambulatory utilization was associated with higher odds (odds ratio=1.85 [95% confidence interval: 1.11‐3.08]), and ambulatory cardiac testing was associated with lower odds (odds ratio=0.73 [0.55‐0.95]) of inpatient AMI mortality, after adjustment for covariates. Asians had higher odds of inpatient AMI mortality even after adjustment for covariates. CONCLUSIONS: Among Medicare fee‐for‐service enrollees, Hispanics and Asians had lower rates of ambulatory care visits, and all minority groups had higher odds of hospitalization for AMI. Ambulatory care utilization, including both ambulatory clinic visits and outpatient cardiac tests, were associated with AMI mortality. Further research is needed to understand the causal relationship between ambulatory care utilization and cardiovascular outcomes.